Entering the nuclear power plant supply chain: The France case study - Locatelli, G.; Mancini, M.; Cocco, G.; Ruzzon, V. (2012 IEEE International Conference on Industrial Engineering and Engineering Management, 2012)
The so called nuclear renaissance is creating a huge market even though the criticality of the supply chain: few firms have the capabilities to work in this complex and demanding market, whereas many other are investigating the option to enter. The international scientific literature provides information regarding the governmental topics of nuclear power programs in different countries, but the analyses at firm level are almost inexistent. In particular it is unclear how an EPC (Engineering, Procurement and Construction) company can enter the supply chain (or project delivery chain). In order to answer this research question the paper investigates the French case study. First it investigates the pure historical facts and shows how French companies developed the national supply chain thanks to a strong governmental support. Then, the typical pattern used in a French NPP project is described analysing the five most relevant companies.